Kinetic Potentials of the Effect of Ethanol on Calcium Content of Ashed Palm Bunch (Elaeis guinensis) (Journal of Basic and Applied Research in Biomedicine, 2022)
The effect of ethanol on the calcium content of ashed palm bunch (Elaeis guineensis) was studied. The palm bunch residue was subjected to pre-treatment processes such as drying, grinding and ashing. The calcium content of the filtered extract of the ash was determined titrimetrically and a concentration of 73.33 mg/l of calcium was recorded. Kinetic studies were carried out on the mixture of local ethanol and the ash extract and the effect of ethanol on calcium concentration was monitored using titrimetric method at 10 minutes interval. The ethanol led to a gradual decrease in the concentration of calcium with increase in time, the rate constant value was 0.67 mgdm3min-1 and half life of 54.97 minutes. Analysis of the kinetic data showed that the reaction was zeroth order as it fitted into the zeroth order integrated rate law. The average pH of the reaction mixture was alkaline (10.57)